Pragmatics and Fiction. - Adams, Jon-K (Pragmatics & beyond, 1985)
Pragmatics and Fiction explores the basic pragmatic differences between fictional and nonfictional discourse. These differences derive mainly from the creation of a fictional figure who narrates the text and who, in turn, addresses his narrative to a fictional audience. Since these figures become the language users of the fictional text and, therefore, displace the actual writer and reader from the communicative context, they dominate the text's pragmatic features. After elaborating a description of fiction from the point of view of these fictional language users, some of the implications for.